PERANCANGAN APLIKASI PERHITUNGAN BIAYA PERAWATAN TANAMAN KELAPA SAWIT PADA PT. LANGKAT NUSANTARA KEPONG (LNK) KEBUN BEKIUN SEBAGAI SOLUSI EFISIENSI BIAYA PERAWATAN - Hidayat, M. Ihsan; Sinurat, Sylvia Natalia; Manik, Ediman; Sihombing, Marto (Majalah Ilmiah Kaputama, 2017)
PT.Langkat Nusantara Kepong (LNK) Bekiun Gardens is one of the state owned enterprises (SOE) in North Sumatra, which is engaged in oil palm plantations, the calculation of plant maintenance costs of palm oil is a series of procedure for calculating the overall costs in plants Palm oil. In this case PT.Langkat Nusantara Kepong (LNK) Gardens Bekiun calculate plant maintenance costs of palm oil are still using Microsoft Excel with this state of affairs is not effective and efficient. With the implementation of the application system maintenance costs calculation may make it easier to perform calculations plant maintenance costs of palm oil to be more disciplined time and data security was more secure. The system is designed using the programming language Microsoft Visual Studio 2010 and SQL Sever 2005 database.Results from this study is the calculation process plant maintenance costs of palm where the design begins with entering data maintenance cost of oil palm trees next admin calculate plant maintenance costs of palm oil and displays them in the form of reports.